2004
DOI: 10.1177/109821400402500407
|View full text |Cite
|
Sign up to set email alerts
|

Written Parental Consent and the Use of Incentives in a Youth Smoking Prevention Trial: A Case Study From Project SPLASH

Abstract: More Institutional Review Boards (IRBs) are requiring written parental consent in school health intervention trials. Because this requirement presents a formidable challenge in conducting largescale research, it is vital for investigators to share effective strategies learned from completed trials. Investigators for the recently completed Project SPLASH (n = 3,716) smoking prevention trial, conducted in 20 Hawaii middle schools, were required to obtain active parental consent for three surveys across 2 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…In interviews with school personnel responsible for recruiting students to a drug and alcohol survey, principals were rated as having more influence on parent decisions regarding their child's participation than were superintendents, school boards or the local mayor 12 . Direct contact with the school principal and school staff to secure their support and endorsement has been recommended by several authors 10,13–15 . During such contacts, it is suggested that researchers outline the following: the importance of the study and any benefits of participation to the school, students and staff; specific staff roles and responsibilities; possible barriers to the recruitment of students; and procedures for contacting the research team 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In interviews with school personnel responsible for recruiting students to a drug and alcohol survey, principals were rated as having more influence on parent decisions regarding their child's participation than were superintendents, school boards or the local mayor 12 . Direct contact with the school principal and school staff to secure their support and endorsement has been recommended by several authors 10,13–15 . During such contacts, it is suggested that researchers outline the following: the importance of the study and any benefits of participation to the school, students and staff; specific staff roles and responsibilities; possible barriers to the recruitment of students; and procedures for contacting the research team 13 …”
Section: Resultsmentioning
confidence: 99%
“…Other contact strategies, such as telephoning parents or guardians to explain the study and participation requirements, are also likely to be effective 12,13 . It should be noted, however, that institutional review boards, research ethics committees and schools typically do not approve requests for access to parental contact details to permit direct telephone or mailed contact 14 …”
Section: Resultsmentioning
confidence: 99%
“…Research and anecdotal evidence indicates a low probability of harm to students as a result of completion of behavioural surveys (Leakey et al ., ; Langhinrichsen‐Rohling et al ., ). This is the experience of the Child Health Promotion Research Centre research team, with no adverse student outcomes from survey completion observed or reported in the conduct of ten large‐scale projects in schools within the last 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the passive consent group were no more likely to report feeling upset than the active group, indicating no increased risk for students without active parental consent. In a two‐year smoking prevention trial no harm to students from participation was observed, and no parental complaints of negative outcomes were received as a result of their child's participation (Leakey et al ., ).…”
Section: Motivation and Aim Of This Studymentioning
confidence: 97%
“…The importance of actively engaging children in the research process is further supported by the work of Leakey et al 27 In a school‐based smoking prevention trial, Leakey et al compared methods to obtain active parental consent for student participation and found that the highest response rates resulted from project staff distributing consent materials in the classroom and providing class‐based incentives. In our study, a parent‐report questionnaire achieved similar results when comparing classroom presentations and questionnaire distribution by research staff to teacher distribution of the questionnaires alone without incentives.…”
Section: Discussionmentioning
confidence: 99%